(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The report presents a conceptual scheme of changing the reaction norm in a population of insect pests. When external conditions stabilize, this may be the main reason for the out breaks of such pests. Taking into account the above, a change in the definition of the r-strategist species is proposed.